2020
DOI: 10.1007/s00330-020-06959-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension due to left heart disease: diagnostic value of pulmonary artery distensibility

Abstract: Objectives To evaluate how pulmonary artery (PA) distensibility performs in detecting pulmonary hypertension due to left heart disease (PH-LHD) in comparison with parameters from ungated computed tomography (CT) and echocardiography. Methods One hundred patients (79 men, mean age = 63 ± 17 years) with either severe heart failure with reduced ejection fraction (HFrEF), aortic stenosis, or primary mitral regurgitation prospectively underwent right heart catheterization, ungated CT, ECG-gated CT, and echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Previous reports have compared the systolic and diastolic diameters of the main pulmonary artery in cardiac motion, thereby assessing pulmonary arterial distensibility [ 3 , 4 , 6 ]. For example, Colin et al have shown that the more advanced pulmonary hypertension due to COPD, the less distensibility it has [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have compared the systolic and diastolic diameters of the main pulmonary artery in cardiac motion, thereby assessing pulmonary arterial distensibility [ 3 , 4 , 6 ]. For example, Colin et al have shown that the more advanced pulmonary hypertension due to COPD, the less distensibility it has [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have compared the systolic and diastolic diameters of the main pulmonary artery in cardiac motion, thereby assessing pulmonary arterial distensibility [ 3 , 4 , 6 ]. For example, Colin et al have shown that the more advanced pulmonary hypertension due to COPD, the less distensibility it has [ 6 ]. However, these studies did not measure the blood vessels four-dimensionally in physiological breathing conditions, because the measurements were made with specific respiratory levels held, or even under respiration, without distinguishing between inhalation and exhalation, and may not reflect normal hemodynamics itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-time detection of the abnormalities in atrial pulses could lead to the prevention of serious cardiac diseases. Monitoring arterial pressure may potentially help in the diagnosis of cardiac and blood diseases 36,37 . This self-powered tattoo-based HWDs is POC in nature and mitigates the high-power consumption required by conventional arterial monitors.…”
Section: E-skin or Tattoo-based Hwdsmentioning
confidence: 99%
“…A relevant new approach was recently published by Sudo et al [55] who related the MPA diameter to the body surface area (PA/BSA) and thus defined a good predictor for PH detection. The extent to which the distensibility of the pulmonary artery, which can be determined in CT diagnostics, has diagnostic value for the assessment of PH [56] remains to be clarified in further studies.…”
Section: Echocardiographymentioning
confidence: 99%